2014
DOI: 10.1189/jlb.5ru0714-360rr
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent role of IL-18 in cancer biology and counter-regulation by IL-18BP

Abstract: IL-18 is a proinflammatory and immune regulatory cytokine, member of the IL-1 family. IL-18 was initially identified as an IFN-γ-inducing factor in T and NK cells, involved in Th1 responses. IL-18 is produced as an inactive precursor (pro-IL-18) that is enzymatically processed into a mature form by Casp1. Different cells, such as macrophages, DCs, microglial cells, synovial fibroblasts, and epithelial cells, express pro-IL-18, and the production of bioactive IL-18 is mainly regulated at the processing level. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 109 publications
3
103
0
3
Order By: Relevance
“…15 In the context of tumor microenvironments, IL-18 has been proposed to have opposing effects: it may promote tumor progression, particularly in the absence of Th1-like cytokines, 8,16,17 or it may promote adaptive immunity with antitumor effect when associated with other cytokines. 13,18 In line with these observations, we could observe a positive correlation between the amount of IL-18 and conventional Th1-associated cytokines (i.e., IFNg, TNF-a and IL-12), especially in TUM district (Fig. 2C), supporting the idea that IL-18 can act as a driver of antitumor Th1-like responses in the NSCLC milieu.…”
Section: Resultssupporting
confidence: 81%
“…15 In the context of tumor microenvironments, IL-18 has been proposed to have opposing effects: it may promote tumor progression, particularly in the absence of Th1-like cytokines, 8,16,17 or it may promote adaptive immunity with antitumor effect when associated with other cytokines. 13,18 In line with these observations, we could observe a positive correlation between the amount of IL-18 and conventional Th1-associated cytokines (i.e., IFNg, TNF-a and IL-12), especially in TUM district (Fig. 2C), supporting the idea that IL-18 can act as a driver of antitumor Th1-like responses in the NSCLC milieu.…”
Section: Resultssupporting
confidence: 81%
“…However, depending on the context and interaction with other cytokines, IL-18 can display various inflammatory activities typical of the other IL-1 family members (Novick et al, 2013). This two-sided nature of IL-18 makes it a double-edged sword in cancer: whereas Th1 cell-promoting activities of IL-18 ensure anti-tumor immune responses, the pro-inflammatory functions of IL-18 might facilitate tumor progression and angiogenesis (Fabbi et al, 2015). Deletion of Il18 in mice results in obesity, insulin resistance, atherosclerosis, and hyperglycemia, which together resemble the features of metabolic syndrome in humans (Netea et al, 2006).…”
Section: Il-18mentioning
confidence: 97%
“…4 were not found in these tumors cells lacking MyD88/NFkB oncogenic signals. Depending on the preclinical models used, the role of the inflammasome in carcinogenesis has been contradictory and context-dependent (27,35). In one colorectal metastasis model, the inflammasome complex was found to suppress metastasis via NK cell activity (45), and others showed that NLRP3 signaling in hematopoietic compartment can be protective against tumorigenesis through bone marrow chimera studies (31,33).…”
Section: Caspase-1 Expression In the Tme Correlates With Worse Prognosismentioning
confidence: 99%
“…The NLRP3 inflammasome complex, in some colorectal carcinoma models, can confer an anticarcinogenic effect (30)(31)(32)(33)(34). However, other murine models in gastric cancers, B16F10 melanoma, colitis-associated colon cancer, and T-ALL have variously shown opposing pro-tumorigenic activities of inflammasome cytokines (35,36). Chemotherapy can further confound the picture to activate the NLRP3 inflammasome to promote tumor growth rate (37).…”
mentioning
confidence: 99%